Hubungan Dukungan Keluarga dengan Kualitas Hidup Pasien HD (Hemodialisa) - Rahim, Nirwanto; Reasioanto, Candra; Katili, Ansar (AACENDIKIA: Journal of Nursing, 2023)
Kidney failure is the cause of death of inpatients at the hospital with a percentage of around 3.8%. The purpose of this study was to identify and analyze the relationship between family support and quality of life for HD patients at Aloei Saboe Hospital, Gorontalo City. This research was conducted using an analytical survey with a cross sectional design. The results obtained are p = 0.000, which means that the p-value is smaller than alpha (5%). the existence of good support from the family will also have a good impact on the quality of life of patients who are undergoing Hemodialysis therapy at the Aloei Saboe Hospital, Gorontalo City. The support provided can be in the form of physical, emotional, instrumental and informational support that can improve the quality of life of patients where they will feel cared for, feel that their lives have meaning, are still able to associate and socialize with friends and their environment and can accept their body and health condition even though it is not like when they were healthy before. There is a relationship between family support and the quality of life of HD patients at Aloei Saboe Hospital, Gorontalo City.